Modeling evacuation in institutional space: Linking three-dimensional data capture, simulation, analysis, and visualization workflows for risk assessment and communication. (January 2019) - Lochhead, Ian M; Hedley, Nick
This article presents exploratory research to develop new workflows that address the challenges of adequately capturing the geometry and topology of complex institutional spaces, the analysis of prescriptive evacuation plans, and the simulation of human movement and behavior in emergency scenarios. We present a collection of geovisual analytical environments that were developed to permit new ways to view and assess risk, evacuation, and human movement. Part of this research considers how different approaches to the representation of complex institutional space, using three-dimensional capture technologies at multiple resolutions (or derived from conventional formats, such as building plans), have implicit advantages or liabilities in the analysis of risk and human evacuation. We combine three-dimensional data capture methods with geographical information science theory, three-dimensional game engines, three-dimensional evacuation simulations and spatial analyses that address the variability of campus populations, and draw upon three-dimensional modeling and photogrammetry for the assessment of real-world features in digital space. The outcome of this research demonstrates agile workflows that address emergency planning requirements, but could also enable enhanced visual analysis and interactive learning by all campus citizens. Furthermore, this work reveals key considerations and limitations associated with the dynamic nature of evacuation events and the static environments in which they have been simulated.